PTU-185 Update On The Halt-it Trial Progress: Tranexamic Acid For The Treatment Of Gastrointestinal Haemorrhage – An International, Randomised, Double Blind Placebo Controlled Trial. (9th June 2014) - Jairath, V; Shakur, H; Edwards, P; Ker, K; Manno, D; Gilmore, I; Veitch, A; Stanworth, S; Coats, T; Roberts, I
Abstract : Introduction: Gastrointestinal (GI) bleeding is a common medical emergency and an important cause of morbidity and mortality in high, middle and low income countries. Despite advances in resuscitative, pharmacological and endoscopic therapy, re-bleeding occurs in 10% of patients with non-variceal bleeding and up to 25% of those with variceal bleeding and is an important predictor of death. Excessive fibrinolysis may play an important role both in the failure to control initial bleeding and in the precipitation of re-bleeding through premature breakdown of blood clots at sites of vascular injury. This raises the possibility that an antifibrinolytic drug administered following GI bleeding could limit severity of bleeding and transfusion requirements. Methods: HALT-IT has been designed as a large, pragmatic randomised controlled trial which aims to quantify the efficacy and safety of tranexamic acid (TXA) in adults with significant acute upper or lower gastrointestinal bleeding. The trial will determine the effect of early administration of TXA on mortality, morbidity, blood transfusion, surgical intervention and health status in patients with GI bleeding. The primary outcome is death in hospital within 28 days of randomisation. Secondary outcomes include re-bleeding, need for surgery or radiological intervention, blood product transfusion and thromboembolic events. Results: UK recruitment began in August 2013. By January 2014, a total of 507 patients were randomised across 26 actively recruiting sites, averaging a recruitment rate of 20 patients per week. Centralised and statistical data monitoring ensures trial participants meet inclusion criteria and allows real time monitoring of event rates for the primary and secondary outcomes. The results will be presented by intention to treat and a pre-specified subgroup analysis will also determine the treatment effect in patients with liver cirrhosis and variceal bleeding. Conclusion: HALT-IT aims to recruit 8000 participants in hospitals worldwide and recruitment is ahead of schedule based upon a strong performance in the UK. The success of the trial to date has been dependent upon multi-disciplinary and societal engagement as well as infrastructural support provided by NIHR research networks. The results will add to our expanding knowledge about the role of tranexamic acid as an agent for patients with significant bleeding. It is anticipated that the full trial results will be available in 2017. Disclosure of Interest: None Declared.